Regulation of Inflammatory Cell Death by Phosphorylation - Xu, Wen; Huang, Yi (Frontiers in Immunology, 2022)
Cell death is a necessary event in multi-cellular organisms to maintain homeostasis by eliminating unrequired or damaged cells. Currently, there are many forms of cell death, and several of them, such as necroptosis, pyroptosis and ferroptosis, even apoptosis trigger an inflammatory response by releasing damage-associated molecular patterns (DAMPs), which are involved in the pathogenesis of a variety of human inflammatory diseases, including autoimmunity disease, diabetes, Alzheimer’s disease and cancer. Therefore, the occurrence of inflammatory cell death must be strictly regulated. Recently, increasing studies suggest that phosphorylation plays a critical role in inflammatory cell death. In this review, we will summarize current knowledge of the regulatory role of phosphorylation in inflammatory cell death and also discuss the promising treatment strategy for inflammatory diseases by targeting related protein kinases that mediate phosphorylation or phosphatases that mediate dephosphorylation.